Microvascular cells: A special focus on heterogeneity of pericytes in diabetes associated complications. (May 2021) - Rajendran, Sharmila; Seetharaman, Shanmuganathan; Dharmarajan, Arun; Kuppan, Kaviarasan
Abstract: Pericytes (PC) are microvascular mural cells that make specific cell-to-cell contacts with the endothelial cells (EC). These cells are obligatory constituents of the microvessels including the retinal vasculature and they serve as regulators of vascular development, stabilization, maturation and remodeling. During early stages of diabetic retinopathy (DR), apoptotic loss of PC surrounding the retinal vasculature occurs. This may lead to reduced vessel stability, the onset of EC apoptosis, and subsequent retinal ischemia leading to angiogenesis and eventually, severe vision loss due to late proliferative diabetic retinopathy (PDR). Similarly, diabetic nephropathy (DN) is a chronic kidney disease due to hyperglycemia that particularly affects renal PC. Chronic high blood glucose level causes migration of peritubular PC away from the capillary into the interstitial space, which destabilizes the micro vessels, resulting in microvascular rarefaction. In both diabetes associated complications, the identification of specific biomarkers is necessary to stabilize the PC at an early stage. This review largely covers the importance of PC towards the pathogenesis of diabetes associated complications, and their heterogeneity in healthy and angiogenic vasculature.